Path to sustainable development. - FIGUERES OLSEN, Jose Maria (1996)
Identifies twelve challenges which sum up the core elements of sustainability, viz: land-use planning, climatic change, biodiversity, conservation areas, education, renewable energy sources, agricultural development, economic policies, environmental management, modernisation and diversification of production, and, the development of democracies.